Plenipotentiary speech Government of the Kyrgyz Republic in Issyk-Kul region Osmonaliev Akylbek Sharipovich (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The abstract is missing.
Keywords: There are no keywords.